Attitude estimation and control of a 3-DOF lab helicopter only based on optical flow. (17th April 2016) - Zhang, Lianhua; Shi, Zongying; Zhong, Yisheng
Abstract : This paper proposes an attitude estimation method based on optical flow to solve the attitude tracking control problem for a three degree-of-freedom (3-DOF) lab helicopter. First, the relationship between optical flow and the motion of a general unmanned aerial vehicle is derived from the transformation between the image coordinate frame and the world coordinate frame. Then, an expression for the angular velocity of the 3-DOF helicopter is deduced only based on optical flow, and the attitude information is acquired by solving nonlinear equations. Finally, using visual feedback, a linear quadratic regulation (LQR) controller is designed for hovering and tracking, which consists of a feedforward controller and a LQR state feedback controller. Closed-loop experimental results on the lab helicopter demonstrate the effectiveness of the proposed estimation and control methods. Graphical Abstract: